Anti-ultraviolet waterproof fabric for casual cap
By using the structure of a modified polyurethane layer, an anti-ultraviolet hydrophobic layer and a moisture-permeable inner lining layer in the cap fabric, and using electrospinning technology and inorganic crosslinking agent, the lack of waterproof and ultraviolet resistance of fabrics in the prior art is solved. Problem, high-performance waterproof, moisture permeable and tensile-resistant effects are achieved.
Patent Information
- Application Number
- CN202411704426.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The waterproof performance and ultraviolet resistance of the fabrics for caps in the prior art need to be further improved.
Using a structure including a modified polyurethane layer, an anti-ultraviolet hydrophobic layer and a moisture permeable inner lining layer, the modified polyurethane layer is prepared by electrospinning technology, combining an inorganic crosslinking agent and an anti-ultraviolet monomer to form excellent waterproof and resistance. UV fabric.
It significantly improves the waterproof, moisture permeability and tensile resistance of the fabric, while enhancing the UV resistance ability to form a high-performance UV waterproof fabric.
Smart Images

Figure BDA0005154192360000031 
Figure BDA0005154192360000041 
Figure BDA0005154192360000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabric processing, and in particular to an anti-ultraviolet waterproof fabric for a leisure hat. Background Art
[0002] The original leisure hats were made of ordinary cotton or polyester, relying on the density of the fabric to simply block ultraviolet rays. They had poor air permeability and limited sun protection effects. As people became more concerned about the hazards of ultraviolet rays, the application of titanium dioxide coatings and ultraviolet absorbers gave the fabrics better sun protection properties. Subsequently, through microporous membranes and hydrophilic coating technology, the fabrics achieved moisture permeability and improved wearing comfort. The development of nanotechnology further improved fabric performance, such as nanofibers and nanopore structures that enhance UV protection and moisture permeability. Today, the emergence of environmentally friendly renewable materials and smart fabrics has given leisure hats more diverse functions and environmentally friendly attributes. The development of moisture-permeable and UV-proof fabrics not only meets health needs, but also brings higher comfort and practicality to leisure hats.
[0003] Prior art CN114274642B discloses a thermoplastic polyurethane fabric and a preparation method and application thereof. The thermoplastic polyurethane fabric comprises a polyurethane base layer, a breathable layer and a waterproof layer which are stacked in sequence. The raw materials for preparing the polyurethane base layer include the following components in parts by weight: 50-60 parts of diisocyanate, 70-100 parts of diol, 1-5 parts of chain extender, 1-3 parts of catalyst, 3-5 parts of hydrogen-containing silicone oil, and the diol comprises polyoxypropylene diol and siloxane diol in a mass ratio of (2-3):1. The thermoplastic polyurethane of the present invention has excellent breathability and waterproofness, and also has a certain anti-ultraviolet ability.
[0004] However, the above patent prepares polyurethane by polymerization, and uses polyurethane to mix with different auxiliary materials to prepare polyurethane base layer, breathable layer and waterproof layer respectively, so as to achieve the effects of waterproof, breathable and UV resistance. However, the polarity difference between polyurethane materials and auxiliary materials is large, which leads to poor dispersion of auxiliary materials, resulting in weak bonding strength of the internal structure of the layers and the bonding strength between the hierarchical structures, which in turn leads to the need to further improve the waterproof performance and UV resistance of the material.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The object of the present invention is to provide an anti-ultraviolet waterproof fabric for a leisure hat, so as to solve the technical problem in the prior art that the waterproof performance and anti-ultraviolet performance of the hat fabric need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: an anti-ultraviolet waterproof fabric for a leisure hat, comprising a modified polyurethane layer, an anti-ultraviolet hydrophobic layer and a moisture permeable lining layer, wherein the modified polyurethane layer is located between the anti-ultraviolet hydrophobic layer and the moisture permeable lining layer;
[0008] Wherein, the preparation method of the modified polyurethane layer comprises the following steps:
[0009] A1. Add modified polyurethane, inorganic crosslinking agent, antibacterial agent, reinforcing agent, plasticizer, crosslinking agent and N,N-dimethylformamide into a reaction kettle, and stir at room temperature for 10-15 minutes to obtain an electrospinning solution;
[0010] A2, adding the electrospinning solution into an electrospinning machine, electrospinning to obtain modified fibers, and performing post-treatment to obtain modified polyurethane fibers;
[0011] A3. Use modified polyurethane fiber to weave to obtain a modified polyurethane layer.
[0012] Furthermore, in step A1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of modified polyurethane, inorganic crosslinker, antibacterial agent, reinforcing agent, plasticizer, crosslinker and N,N-dimethylformamide is 12-15g:2-3g:0.5-0.8g:0.5-0.8g:0.5-0.8g:0.3-0.5g:70-80mL; in step A2, the electrospinning operation includes: pouring the electrospinning solution into the ejector of the electrospinning machine, setting the voltage of the electrospinning machine to 15-25kV, setting the spinning distance to 10-20cm, controlling the flow rate at 0.5-1L / h, and spinning to obtain modified fibers.
[0013] Furthermore, in step A2, post-treatment includes: transferring the modified fiber to a drying oven at a temperature of 80°C and vacuum drying the fiber until the fiber has a constant weight to obtain a modified polyurethane fiber; in step A3, the weaving operation includes: selecting 100-150D modified polyurethane fiber, the number of monofilaments is 36-48F, setting the twist of the yarn to 400-600 twists / m, the twist direction is Z twist, and after twisting, heat setting at a temperature of 180-200°C, and winding at a speed of 600-700m / min to obtain the yarn, the yarns are used as warp yarns and weft yarns, respectively, and weaving to obtain a modified polyurethane layer; the warp yarn has an imperial count of 40-50s, the weft yarn has an imperial count of 35-45s, and the density of the modified polyurethane layer is 160-180 warp yarns and 100-120 weft yarns per square inch.
[0014] Furthermore, the antibacterial agent is one or more of benzalkonium chloride, polyhexamethyleneguanidine and tetradecyltrimethylammonium chloride; the reinforcing agent is one or more of nano-silica, carbon fiber and nano-alumina; the plasticizer is one or more of dibutyl phthalate, triethyl citrate and dioctyl adipate; the cross-linking agent is one or more of hexamethylene diisocyanate, glycidyl methacrylate and melamine formaldehyde resin.
[0015] Further, the preparation method of the modified polyurethane comprises the following steps:
[0016] B1. Add 2,4-dihydroxybenzophenone, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stir. The temperature of the reaction kettle is raised to 50-60° C., 3,3-dichlorobiphenyl 4,4-diisocyanate solution is added dropwise into the reaction kettle, and the reaction is carried out by heat preservation for 40-60 minutes. An inorganic crosslinking agent is added into the reaction kettle, and the reaction is carried out by heat preservation for 20-30 minutes to obtain a composite polyurethane solution.
[0017] The reaction equation for preparing the composite polyurethane solution is:
[0018]
[0019] Where:
[0020]
[0021] The reaction principle for preparing the composite polyurethane solution is as follows: the hydroxyl groups on 2,4-dihydroxybenzophenone and the isocyanate groups on 3,3-dichlorobiphenyl 4,4-diisocyanate undergo polymerization reaction under the catalysis of a catalyst, and polyurethane chain segments terminated with isocyanate groups are finally prepared by continuous polymerization and control of the amount of reactants, and react with an inorganic cross-linking agent to produce a complex spatial chain segment structure, and finally a composite polyurethane solution is prepared.
[0022] B2. Add the composite polyurethane solution, 3-trifluoromethylpropiophenone, acetic acid and tetrahydrofuran into the reaction kettle, increase the temperature of the reaction kettle to 40-50° C., keep the temperature for 2-4 hours, and perform post-treatment to obtain the modified polyurethane.
[0023] The reaction principle for preparing the modified polyurethane is as follows: under the catalysis of acetic acid and heating, the ketone groups on 3-trifluoromethylpropiophenone and the composite polyurethane chain segments undergo Schiff base formation reaction to produce crosslinking, and finally the modified polyurethane is prepared.
[0024] Further, in step B1, the stirring rate of the reactor is 80-120 rpm, and the amount ratio of 2,4-dihydroxybenzophenone, N,N-dimethylformamide, dibutyltin dilaurate, 3,3-dichlorobiphenyl 4,4-diisocyanate solution and inorganic crosslinking agent is 3-5 g: 20-30 mL: 0.1-0.3 g: 10-15 mL: 2-4 g, and the 3,3-dichlorobiphenyl 4,4-diisocyanate solution is composed of 3,3-dichlorobiphenyl 4,4-diisocyanate and N,N-dimethylformamide is prepared in a dosage ratio of 2-3g:6-10mL; in step B2, the dosage ratio of the composite polyurethane solution, 3-trifluoromethylpropiophenone, acetic acid and tetrahydrofuran is 8-10g:2-4g:0.3-0.5g:50-60mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a modified polyurethane.
[0025] Further, the preparation method of the inorganic crosslinking agent comprises the following steps:
[0026] C1. Add butyl titanate and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 50-60°C, use 1-2 mol / L ammonia solution to adjust the pH of the system to 8-9. Keep the temperature for 36-48 hours to obtain titanium gel, and then post-treat to obtain nano titanium dioxide particles.
[0027] C2. Add nano titanium dioxide particles, N-aminoethyl-3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and anhydrous ethanol into a reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain an inorganic crosslinking agent.
[0028] The reaction equation for preparing the inorganic crosslinking agent is:
[0029]
[0030] The reaction principle for preparing the inorganic crosslinking agent is as follows: under alkaline conditions and the catalysis of heating, the siloxy groups on N-aminoethyl-3-aminopropyltriethoxysilane are hydrolyzed to produce silanol structures, which react with the hydroxyl groups on the surface of nano-titanium dioxide particles to finally prepare the inorganic crosslinking agent.
[0031] Furthermore, in step C1, the stirring rate of the reactor is 80-120rpm, the dosage ratio of butyl titanate, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL, and the post-treatment includes: adding the titanium gel to a tubular furnace, introducing nitrogen protection, heating the tubular furnace to 750-850°C at a heating rate of 3-5°C / min, and calcining for 4-6h to obtain nano titanium dioxide particles; in step C2, the dosage ratio of nano titanium dioxide particles, N-aminoethyl-3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and anhydrous ethanol is 6-8g:2-3g:0.3-0.5mL:30-40mL, and the post-treatment includes: filtering the reaction solution, collecting the filter cake, washing it with anhydrous ethanol and deionized water for 3-5 times, and then placing the filter cake in a drying oven at a temperature of 60°C for vacuum drying to obtain an inorganic crosslinking agent.
[0032] Furthermore, the preparation method of the UV-resistant hydrophobic layer comprises the following steps:
[0033] D1, add trans-3-(trimethylsilyl)allyl alcohol, 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, azobisisobutyronitrile and dimethyl sulfoxide into a reaction kettle, raise the temperature of the reaction kettle to 70-80°C, keep the temperature for 2-4 hours, and obtain a modified liquid precursor;
[0034] The reaction equation for preparing the modified precursor solution is:
[0035]
[0036] Where:
[0037] The reaction principle for preparing the modified precursor liquid is as follows: under high temperature and the catalysis of a free radical initiator, the double bonds of trans-3-(trimethylsilyl)allyl alcohol, 2-(perfluorohexyl)ethyl methacrylate and acrylic acid are broken to generate free radicals, and through continuous polymerization, a modified liquid precursor is finally prepared.
[0038] D2, adding the modified precursor liquid, 2,4-dihydroxybenzophenone and triethylamine into the reaction kettle, raising the temperature of the reaction kettle to 50-60°C, and keeping the temperature for 20-30 minutes to obtain the modified liquid;
[0039] The reaction equation for preparing the modified liquid is:
[0040]
[0041] Where:
[0042] The reaction principle for preparing the modified liquid is as follows: under the catalysis of high temperature and alkaline conditions, the carbonyl carbon in the carboxyl group has positive charge, and as an electrophilic center, the nitrogen atom in the carbon-nitrogen double bond carries a lone pair of electrons, and acts as a nucleophilic reagent to perform nucleophilic addition on the carboxyl group to generate a transition state, and eventually the carbon-nitrogen double bond breaks, the carbonyl and amino groups are cross-linked, and finally the modified liquid is prepared.
[0043] D3. Place the modified polyurethane layer in a mold, mix the hydrophobic liquid and evenly coat the surface of the modified polyurethane layer with a coating thickness of 40-50 μm, and cure at high temperature to obtain an anti-ultraviolet hydrophobic layer.
[0044] The reaction principle for preparing the UV-resistant hydrophobic layer is as follows: during the high-temperature curing process, the acetic acid component in the hydrophobic liquid promotes the reaction between the ketone group in the modified liquid and the imino group in the modified polyester layer, forming a stable structure cross-linked by chemical bonds, and finally the UV-resistant hydrophobic layer is prepared by curing.
[0045] Further, in step D1, the amount ratio of trans-3-(trimethylsilyl)allyl alcohol, 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, azobisisobutyronitrile and dimethyl sulfoxide is 4-5g:8-10g:2-3g:0.3-0.5g:60-80mL; in step D2, the amount ratio of modified precursor solution, 2,4-dihydroxybenzophenone and triethylamine is 15-20mL:2-3g:0.3-0.5g; in step D3, the hydrophobic liquid is prepared by mixing the modified liquid and acetic acid in an amount ratio of 50-60mL:3-5mL, and the operation of high temperature curing is as follows: placing the material in a drying oven, passing nitrogen protection, raising the temperature of the drying oven to 100-120°C, and keeping warm until the material has a constant weight to obtain an anti-ultraviolet hydrophobic layer.
[0046] Furthermore, the preparation method of the moisture permeable lining layer (300) is as follows: after placing the anti-ultraviolet hydrophobic layer toward the bottom of the mold, adding the modified moisture permeable liquid into the atomizer, spraying it onto the modified polyurethane layer after atomization, with a spraying thickness of 15-20 μm, and obtaining the moisture permeable lining layer after curing.
[0047] The reaction principle for preparing the moisture permeable inner lining layer is as follows: during the curing process of the modified moisture permeable liquid, the polyethylene glycol undergoes thermal decomposition and evaporates together with the solvent, eventually forming a void structure to obtain the moisture permeable inner lining layer.
[0048] Furthermore, the modified breathable liquid is prepared by mixing polyurethane, polyacrylic resin, polyethylene glycol and deionized water in a dosage ratio of 50-60g:10-20g:2-5g:20-30mL, and the curing operation is as follows: placing the material in a drying oven, introducing nitrogen protection, raising the temperature of the drying oven to 60°C, and after heat preservation for 10-15 minutes, raising the temperature of the drying oven to 100°C, and keeping warm until the material reaches constant weight to obtain a breathable lining layer.
[0049] The present invention has the following beneficial effects:
[0050] 1. The surface of the inorganic crosslinking agent prepared by the present invention is modified with a large number of amino groups. The amino groups serve as crosslinking groups to promote the crosslinking of polyurethane segments and improve the tensile strength of the fabric. The ultraviolet protection effect of the inorganic crosslinking agent itself and the modified polyurethane synthesized with anti-ultraviolet monomers and the modified liquid modified with anti-ultraviolet monomers work together to improve the anti-ultraviolet ability of the material. In addition, as conductive metal oxide particles, the process of electrostatic spinning is promoted. The modified polyurethane modified with hydrophobic groups and the modified liquid are combined to significantly improve the waterproof performance of the material. The hydrophilic pore structure of the lining moisture permeable layer and the external hierarchical structure form an adsorption-transfer-desorption process for moisture, which promotes the discharge of sweat and significantly improves the moisture permeability of the fabric. Finally, a waterproof, moisture permeable, and stretch-resistant anti-ultraviolet fabric is prepared.
[0051] 2. The present invention also prepares nano titanium dioxide particles by hydrolysis, and modifies a large number of amino groups on the surface. The particles themselves enhance the material's anti-ultraviolet ability. In the process of preparing the modified polyurethane, the amino groups are used as cross-linking groups to hybridize the spatial chain segments of the polyurethane, which significantly improves the material's tensile resistance. When the modified cross-linking agent is evenly dispersed in the modified polyurethane, the modified cross-linking agent adjusts the conductivity of the spinning solution during electrospinning, making it easier for the electrostatic force to act on the solution, thereby improving the spinning efficiency, and improving the charge transfer efficiency of the solution, forming a stable electrostatic field, promoting the injection speed and uniform formation of the fiber, and enhancing the charge distribution of the spinning solution and the uniformity of the stretching process, reducing these bead defects, thereby improving the spinning efficiency, and forming more uniform and continuous fibers; in the process of preparing the modified polyurethane layer by weaving, the yarn gap is controlled, and the pore structure in the moisture permeable lining layer produces an adsorption-transfer-desorption process for moisture, which promotes the discharge of moisture and significantly improves the moisture permeability of the material.
[0052] 3. In the process of preparing the modified polyurethane layer of the present invention, 2,4-dihydroxybenzophenone as an ultraviolet absorber UV-0 is first selected as a reaction monomer, and a polyurethane segment with certain ultraviolet resistance is synthesized and prepared, and a modified polyurethane with significant ultraviolet resistance is formed by crosslinking with an inorganic crosslinking agent with excellent ultraviolet resistance, and then modified by a fluorine group, and coordinated with the hydrophobic group on the surface of the inorganic crosslinking agent to give the material excellent waterproof performance, and finally the inorganic crosslinking agent promotes electrostatic spinning to obtain a modified polyurethane fiber, and finally the moisture-permeable and waterproof anti-ultraviolet modified polyurethane layer is obtained by controlling the spinning gap by weaving; in the process of modifying the modified polyurethane layer to obtain the anti-ultraviolet hydrophobic layer, firstly, by selecting the monomer, a modified liquid precursor is synthesized and prepared, and further modifying the anti-ultraviolet group on the segment significantly enhances the anti-ultraviolet ability of the material, and the polymer segment has a perfluorinated segment, so that the anti-ultraviolet hydrophobic layer has excellent waterproof ability, and finally, through the coordinated cooperation of the materials between the hierarchical structure and the apparent structure, the fabric is finally given excellent anti-ultraviolet, waterproof, moisture permeable and tensile properties. DETAILED DESCRIPTION
[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] The polyurethane used in the present invention was purchased from Hangzhou Hemeng Chemical Co., Ltd., with the product number W-6110;
[0055] The polyacrylic acid resin used in the present invention was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with a product number of S51652-500ml.
[0056] Example 1
[0057] This embodiment provides a method for preparing an anti-ultraviolet waterproof fabric for a leisure hat, comprising the following steps:
[0058] S1. Preparation of inorganic crosslinking agent
[0059] Weigh: 9.0g of butyl titanate and 36.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 15min, 24.0mL of deionized water is continuously added dropwise. After the temperature of the reactor is raised to 50°C, a 1.0mol / L ammonia solution is used to adjust the pH value of the system to 8, and the temperature is kept for 36h to obtain a titanium gel. The titanium gel is added to a tubular furnace, and after nitrogen protection is introduced, the tubular furnace is heated to 750°C at a heating rate of 3°C / min, and the temperature is kept for calcination for 4h to obtain nano titanium dioxide particles;
[0060] Weigh: 12.4 g of nano titanium dioxide particles, 4.8 g of N-aminoethyl-3-aminopropyltriethoxysilane, 0.8 mL of saturated sodium hydroxide solution and 72.0 mL of anhydrous ethanol, add into a reactor, raise the temperature of the reactor to 30°C, keep warm for 3 hours, filter the reaction liquid, collect the filter cake, wash it three times with anhydrous ethanol and deionized water, and then place the filter cake in a drying oven at 60°C for vacuum drying to obtain an inorganic cross-linking agent.
[0061] S2. Preparation of modified polyurethane
[0062] Weigh: 5.4 g of 3,3-dichlorobiphenyl 4,4-diisocyanate and 18.0 mL of N,N-dimethylformamide to prepare a 3,3-dichlorobiphenyl 4,4-diisocyanate solution;
[0063] Weigh: 8.4 g of 2,4-dihydroxybenzophenone, 48.0 mL of N,N-dimethylformamide and 0.4 g of dibutyltin dilaurate are added to a reactor and stirred at a stirring rate of 80 rpm. The temperature of the reactor is raised to 50° C. 24.0 mL of 3,3-dichlorobiphenyl 4,4-diisocyanate solution is added dropwise to the reactor and the reaction is carried out at the temperature for 40 minutes. 6.4 g of an inorganic crosslinking agent is added to the reactor and the reaction is carried out at the temperature for 20 minutes to obtain a composite polyurethane solution;
[0064] Weigh: 18.0g of composite polyurethane solution, 7.2g of 3-trifluoromethylpropiophenone, 0.8g of acetic acid and 108.0mL of tetrahydrofuran are added to the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 2h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0065] S3. Preparation of modified liquid
[0066] Weigh: 8.4 g of trans-3-(trimethylsilyl)allyl alcohol, 18.0 g of 2-(perfluorohexyl)ethyl methacrylate, 4.8 g of acrylic acid, 0.8 g of azobisisobutyronitrile and 150.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 70° C., and keep the temperature for 2 hours to obtain a modified liquid precursor;
[0067] Weigh: 36.0 mL of modified precursor solution, 5.4 g of 2,4-dihydroxybenzophenone and 0.8 g of triethylamine, add into the reaction kettle, raise the temperature of the reaction kettle to 50° C., keep warm and react for 20 minutes to obtain the modified solution.
[0068] S4. Preparation of UV-resistant and waterproof fabrics
[0069] Weigh: 12.0 g of modified polyurethane, 2.4 g of inorganic crosslinking agent, 1.2 g of tetradecyltrimethylammonium chloride, 1.2 g of nano-alumina, 1.6 g of triethyl citrate, 0.8 g of hexamethylene diisocyanate and 150.0 mL of N,N-dimethylformamide, add into a reaction kettle and stir at a rate of 80 rpm for 10 min at room temperature to obtain an electrospinning solution;
[0070] The electrospinning solution is added into the electrospinning machine, and the electrospinning solution is poured into the ejector of the electrospinning machine, the voltage of the electrospinning machine is set to 15 kV, the spinning distance is set to 10 cm, the flow rate is controlled at 0.5 L / h, and the modified fiber is spun to obtain the modified fiber, and the modified fiber is transferred to a drying oven at a temperature of 80° C. and vacuum dried until the fiber has a constant weight, thereby obtaining a modified polyurethane fiber;
[0071] A 150D modified polyurethane fiber is selected, the number of monofilaments is 48F, the twist of the yarn is set to 600 twists / m, the twist direction is Z twist, and after twisting, heat setting is performed at a temperature of 200°C, and the yarn is wound at a speed of 700m / min to obtain the yarn, the yarn is used as the warp yarn and the weft yarn respectively, the British count of the warp yarn is 50s, and the British count of the weft yarn is 45s, the density of the modified polyurethane layer is 180 warp yarns per square inch and 120 weft yarns per square inch, and the modified polyurethane layer is woven;
[0072] Weigh: 100.0 mL of modified liquid and 8.0 mL of acetic acid to prepare a hydrophobic liquid;
[0073] The modified polyurethane layer 100 is placed in a mold, and the modified liquid and acetic acid are mixed and evenly coated on the surface of the modified polyurethane layer, with a coating thickness of 40 μm. The material is placed in a drying oven, and after nitrogen protection is introduced, the temperature of the drying oven is increased to 100° C. and kept warm until the material has a constant weight, thereby obtaining an anti-ultraviolet hydrophobic layer 200;
[0074] Weigh: 50.0 g of polyurethane, 16.0 g of polyacrylic acid resin, 3.6 g of polyethylene glycol and 24.0 mL of deionized water to prepare a modified moisture permeable liquid;
[0075] After placing the anti-ultraviolet hydrophobic layer toward the bottom of the mold, add the modified breathable liquid into the atomizer, spray it onto the modified polyurethane layer after atomization, and the spraying thickness is 15 μm. Place the material in a drying oven, and after nitrogen protection, the temperature of the drying oven is increased to 60°C. After heat preservation for 10 minutes, the temperature of the drying oven is increased to 100°C, and the temperature is kept until the material has a constant weight to obtain a breathable lining layer of 300, and finally prepare an anti-ultraviolet waterproof fabric.
[0076] Example 2
[0077] This embodiment provides a method for preparing an anti-ultraviolet waterproof fabric for a leisure hat, comprising the following steps:
[0078] S1. Preparation of inorganic crosslinking agent
[0079] Weigh: 10.0g of butyl titanate and 64.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 80rpm. After stirring at room temperature for 15min, 36.0mL of deionized water is continuously added dropwise. After the temperature of the reactor is raised to 50°C, a 1.6mol / L ammonia solution is used to adjust the pH value of the system to 9, and the temperature is kept for 48h to obtain a titanium gel. The titanium gel is added to a tubular furnace, and after nitrogen protection is introduced, the tubular furnace is heated to 850°C at a heating rate of 5°C / min, and the temperature is kept for calcination for 6h to obtain nano titanium dioxide particles;
[0080] Weigh: 16.0 g of nano titanium dioxide particles, 6.0 g of N-aminoethyl-3-aminopropyltriethoxysilane, 0.8 mL of saturated sodium hydroxide solution and 7.2 mL of anhydrous ethanol, add into a reactor, raise the temperature of the reactor to 30°C, keep warm for 3 hours, filter the reaction liquid, collect the filter cake, wash it three times with anhydrous ethanol and deionized water, and then place the filter cake in a drying oven at 60°C for vacuum drying to obtain an inorganic cross-linking agent.
[0081] S2. Preparation of modified polyurethane
[0082] Weigh: 5.4 g of 3,3-dichlorobiphenyl 4,4-diisocyanate and 18.0 mL of N,N-dimethylformamide to prepare a 3,3-dichlorobiphenyl 4,4-diisocyanate solution;
[0083] Weigh: 8.4 g of 2,4-dihydroxybenzophenone, 54.0 mL of N,N-dimethylformamide and 0.5 g of dibutyltin dilaurate are added to a reactor and stirred at a stirring rate of 80 rpm. The temperature of the reactor is raised to 50° C. 24.0 mL of 3,3-dichlorobiphenyl 4,4-diisocyanate solution is added dropwise to the reactor and the reaction is carried out at the temperature for 40 min. 7.2 g of an inorganic crosslinking agent is added to the reactor and the reaction is carried out at the temperature for 20 min to obtain a composite polyurethane solution.
[0084] Weigh: 18.0g of composite polyurethane solution, 7.2g of 3-trifluoromethylpropiophenone, 0.8g of acetic acid and 100.0mL of tetrahydrofuran are added to the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 2h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0085] S3. Preparation of modified liquid
[0086] Weigh: 8.4 g of trans-3-(trimethylsilyl)allyl alcohol, 16.0 g of 2-(perfluorohexyl)ethyl methacrylate, 5.4 g of acrylic acid, 0.8 g of azobisisobutyronitrile and 150.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 70° C., and keep the temperature for 2 hours to obtain a modified liquid precursor;
[0087] Weigh: 32.0 mL of modified precursor solution, 5.4 g of 2,4-dihydroxybenzophenone and 0.8 g of triethylamine and add them into the reactor. The temperature of the reactor is raised to 50° C. and the reaction is kept warm for 20 minutes to obtain a modified solution.
[0088] S4. Preparation of UV-resistant and waterproof fabrics
[0089] Weigh: 15.0 g of modified polyurethane, 2.4 g of inorganic crosslinking agent, 1.2 g of tetradecyltrimethylammonium chloride, 1.2 g of nano-alumina, 1.6 g of triethyl citrate, 0.8 g of hexamethylene diisocyanate and 70.0 mL of N,N-dimethylformamide, add into a reaction kettle and stir at a rate of 80 rpm for 15 min at room temperature to obtain an electrospinning solution;
[0090] The electrospinning solution is added into the electrospinning machine, and the electrospinning solution is poured into the ejector of the electrospinning machine, the voltage of the electrospinning machine is set to 25 kV, the spinning distance is set to 20 cm, the flow rate is controlled at 1.0 L / h, and the modified fiber is spun to obtain the modified fiber, and the modified fiber is transferred to a drying oven at a temperature of 80° C. and vacuum dried until the fiber has a constant weight, thereby obtaining the modified polyurethane fiber;
[0091] A 100D modified polyurethane fiber is selected, the number of monofilaments is 36F, the twist of the yarn is set to 400 twists / m, the twist direction is Z twist, and after twisting, heat setting is performed at a temperature of 180°C, and winding is performed at a speed of 600m / min to obtain a yarn, and the yarn is used as a warp yarn and a weft yarn, respectively, and the modified polyurethane layer is woven; the British count of the warp yarn is 40s, the British count of the weft yarn is 35s, and the density of the modified polyurethane layer is 160 warp yarns and 100 weft yarns per square inch;
[0092] Weigh: 100.0 mL of modified liquid and 8.0 mL of acetic acid to prepare a hydrophobic liquid;
[0093] The modified polyurethane layer 100 is placed in a mold, and the modified liquid and acetic acid are mixed and evenly coated on the surface of the modified polyurethane layer, with a coating thickness of 50 μm. The material is placed in a drying oven, and after nitrogen protection is introduced, the temperature of the drying oven is increased to 120° C. and kept warm until the material has a constant weight, thereby obtaining an anti-ultraviolet hydrophobic layer 200;
[0094] Weigh: 54.0 g of polyurethane, 18.0 g of polyacrylic acid resin, 4.8 g of polyethylene glycol and 30.0 mL of deionized water to prepare a modified moisture permeable liquid;
[0095] After placing the anti-ultraviolet hydrophobic layer toward the bottom of the mold, add the modified moisture permeable liquid into the atomizer, spray it onto the modified polyurethane layer after atomization, and the spraying thickness is 20 μm. Place the material in a drying oven, and after nitrogen protection, the temperature of the drying oven is increased to 60°C. After heat preservation for 15 minutes, the temperature of the drying oven is increased to 100°C, and the material is kept warm until the weight is constant to obtain a moisture permeable lining layer of 300, and finally the anti-ultraviolet waterproof fabric is prepared.
[0096] Example 3
[0097] This embodiment provides a method for preparing an anti-ultraviolet waterproof fabric for a leisure hat, comprising the following steps:
[0098] S1. Preparation of inorganic crosslinking agent
[0099] Weigh: 12.0g of butyl titanate and 80.0mL of anhydrous ethanol are added to a reactor and stirred at a stirring rate of 100rpm. After stirring at room temperature for 18min, 36.0mL of deionized water is continuously added dropwise. After the temperature of the reactor is raised to 60°C, a 2.0mol / L ammonia solution is used to adjust the pH of the system to 9, and the temperature is kept for 42h to obtain a titanium gel. The titanium gel is added to a tubular furnace, and after nitrogen protection is introduced, the tubular furnace is heated to 800°C at a heating rate of 5°C / min, and the temperature is kept for calcination for 6h to obtain nano titanium dioxide particles;
[0100] Weigh: 14.8 g of nano titanium dioxide particles, 5.4 g of N-aminoethyl-3-aminopropyltriethoxysilane, 0.8 mL of saturated sodium hydroxide solution and 72.0 mL of anhydrous ethanol, add into a reactor, raise the temperature of the reactor to 40°C, keep warm for 4 hours, filter the reaction liquid, collect the filter cake, wash it 4 times with anhydrous ethanol and deionized water, and then place the filter cake in a drying oven at 60°C for vacuum drying to obtain an inorganic cross-linking agent.
[0101] S2. Preparation of modified polyurethane
[0102] Weigh: 5.4 g of 3,3-dichlorobiphenyl 4,4-diisocyanate and 18.0 mL of N,N-dimethylformamide to prepare a 3,3-dichlorobiphenyl 4,4-diisocyanate solution;
[0103] Weigh: 8.4 g of 2,4-dihydroxybenzophenone, 54.0 mL of N,N-dimethylformamide and 0.5 g of dibutyltin dilaurate are added to a reactor and stirred at a stirring rate of 100 rpm. The temperature of the reactor is raised to 55° C. 24.0 mL of 3,3-dichlorobiphenyl 4,4-diisocyanate solution is added dropwise to the reactor and the reaction is carried out at the temperature for 50 min. 7.2 g of an inorganic crosslinking agent is added to the reactor and the reaction is carried out at the temperature for 25 min to obtain a composite polyurethane solution.
[0104] Weigh: 18.0g of composite polyurethane solution, 7.2g of 3-trifluoromethylpropiophenone, 0.8g of acetic acid and 100.0mL of tetrahydrofuran are added to the reactor, the temperature of the reactor is raised to 45°C, and the reaction is kept warm for 3h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0105] S3. Preparation of modified liquid
[0106] Weigh: 8.4 g of trans-3-(trimethylsilyl)allyl alcohol, 18.0 g of 2-(perfluorohexyl)ethyl methacrylate, 5.4 g of acrylic acid, 0.8 g of azobisisobutyronitrile and 150.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 75° C., and keep the temperature for 3 hours to obtain a modified liquid precursor;
[0107] Weigh: 36.0 mL of modified precursor solution, 5.4 g of 2,4-dihydroxybenzophenone and 0.8 g of triethylamine are added into a reactor, the temperature of the reactor is raised to 55° C., and the reaction is kept warm for 20 minutes to obtain a modified solution.
[0108] S4. Preparation of UV-resistant and waterproof fabrics
[0109] Weigh: 14.4 g of modified polyurethane, 5.4 g of inorganic crosslinking agent, 1.2 g of tetradecyltrimethylammonium chloride, 1.6 g of nano-alumina, 1.6 g of triethyl citrate, 0.8 g of hexamethylene diisocyanate and 150.0 mL of N,N-dimethylformamide, add into a reaction kettle and stir at a rate of 100 rpm for 12 min at room temperature to obtain an electrospinning solution;
[0110] The electrospinning solution is added into the electrospinning machine, and the electrospinning solution is poured into the ejector of the electrospinning machine, the voltage of the electrospinning machine is set to 20 kV, the spinning distance is set to 16 cm, the flow rate is controlled at 0.8 L / h, and the modified fiber is spun to obtain the modified fiber, and the modified fiber is transferred to a drying oven at a temperature of 80° C. and vacuum dried until the fiber has a constant weight, thereby obtaining the modified polyurethane fiber;
[0111] A 125D modified polyurethane fiber is selected, the number of monofilaments is 42F, the twist of the yarn is set to 500 twists / m, the twist direction is Z twist, and after the twisting is completed, heat setting is performed at a temperature of 190°C, and the yarn is wound at a speed of 650m / min to obtain the yarn, the yarn is used as the warp yarn and the weft yarn respectively, the British count of the warp yarn is 45s, and the British count of the weft yarn is 40s, the density of the modified polyurethane layer is 170 warp yarns per square inch and 110 weft yarns per square inch, and the modified polyurethane layer is woven;
[0112] Weigh: 54.0 mL of modified liquid and 4.8 mL of acetic acid to prepare a hydrophobic liquid;
[0113] The modified polyurethane layer 100 is placed in a mold, and the modified liquid and acetic acid are mixed and evenly coated on the surface of the modified polyurethane layer, with a coating thickness of 42 μm. The material is placed in a drying oven, and after nitrogen protection is introduced, the temperature of the drying oven is increased to 110° C. and kept warm until the material has a constant weight, thereby obtaining an anti-ultraviolet hydrophobic layer 200;
[0114] Weigh: 54.0 g of polyurethane, 18.0 g of polyacrylic acid resin, 4.8 g of polyethylene glycol and 48.0 mL of deionized water to prepare a modified moisture permeable liquid;
[0115] After placing the anti-ultraviolet hydrophobic layer toward the bottom of the mold, add the modified moisture permeable liquid into the atomizer, spray it onto the modified polyurethane layer after atomization, and the spraying thickness is 18μm. Place the material in a drying oven, and after nitrogen protection, the temperature of the drying oven is increased to 60°C. After heat preservation for 12 minutes, the temperature of the drying oven is increased to 100°C, and the material is kept warm until the weight is constant to obtain a moisture permeable lining layer of 300, and finally the anti-ultraviolet waterproof fabric is prepared.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 3 is that the step of preparing an inorganic crosslinking agent in step S1 is eliminated, and in the process of preparing a composite polyurethane solution in step S2, an equal amount of nano titanium dioxide particles are used to replace the inorganic crosslinking agent.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 3 is that the step of preparing modified polyurethane in step S2 is eliminated, and in the process of preparing electrospinning solution in step S4, an equal amount of composite polyurethane solution is used to replace modified polyurethane.
[0120] Comparative Example 3
[0121] The difference between this comparative example and Example 3 is that the step of preparing modified polyurethane in step S3 is eliminated, and in the process of preparing the anti-ultraviolet hydrophobic layer in step S4, molten polyvinylidene fluoride is used to replace the modifying liquid in an equal amount.
[0122] Performance Test:
[0123] The hydrostatic pressure, moisture permeability, breaking strength and water sticking grade of the anti-ultraviolet waterproof fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard FZ / T 14057-2023 "Nylon-Spandex Waterproof and Breathable Composite Fabrics";
[0124] With reference to standard HG / T 4735-2014 "Determination of anti-ultraviolet performance of anti-ultraviolet finishing agents for textile dyeing and finishing", the ultraviolet protection factor and ultraviolet transmittance of the anti-ultraviolet waterproof fabrics prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 for specific data.
[0125] Table 1-Performance test data of each sample
[0126]
[0127] Data Analysis:
[0128] Comparative analysis of the data in Table 1 above shows that the hydrostatic pressure of the anti-ultraviolet waterproof fabric prepared by the present invention is 58.3 kPa, and the moisture permeability is 8963 g·(m 2 24h) -1 , breaking strength of 565N, water sticking level of 4, UV protection factor of 59 and UV transmittance of only 1.8%; By comparing the data of Example 3 and Comparative Example 1, it can be found that the hybridization of the polyurethane chain segment by the inorganic crosslinking agent and the supplement of the hydrophobic groups on the surface of the inorganic crosslinking agent are missing, and the breaking strength and UV protection factor of the anti-UV waterproof fabric are significantly reduced; By comparing the data of Example 3 and Comparative Example 2, it can be found that the hydrophobic modification of the polyurethane chain segment in the composite polyurethane solution is missing, and the hydrostatic pressure and water-wetting level of the anti-UV waterproof fabric are significantly reduced; By comparing the data of Example 3 and Comparative Example 3, it can be found that after using molten polyvinylidene fluoride to replace the modifying liquid in equal amounts, although the waterproof performance decreases slightly, the anti-UV ability decreases significantly; The data of the embodiments are due to the comparative example,
[0129] The surface of the inorganic crosslinking agent prepared by the present invention is modified with a large number of amino groups. The amino groups serve as crosslinking groups to promote the crosslinking of polyurethane segments and improve the tensile strength of the fabric. The ultraviolet protection effect of the inorganic crosslinking agent itself and the modified polyurethane synthesized with anti-ultraviolet monomers and the modified liquid modified with anti-ultraviolet monomers work together to improve the anti-ultraviolet ability of the material. The conductive metal oxide particles promote the process of electrostatic spinning. The modified polyurethane modified with hydrophobic groups and the modified liquid significantly improve the waterproof performance of the material. The hydrophilic pore structure of the lining moisture permeable layer and the external hierarchical structure form an adsorption-transfer-desorption process for moisture, which promotes the discharge of sweat and significantly improves the moisture permeability of the fabric. Finally, a waterproof, moisture permeable, and stretch-resistant anti-ultraviolet fabric is prepared.
[0130] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An anti-ultraviolet waterproof fabric for a leisure hat, characterized in that: It comprises a modified polyurethane layer, an anti-ultraviolet hydrophobic layer and a moisture permeable inner lining layer, wherein the modified polyurethane layer is located between the anti-ultraviolet hydrophobic layer and the moisture permeable inner lining layer; Wherein, the preparation method of the modified polyurethane layer comprises the following steps: A1. Add modified polyurethane, inorganic crosslinking agent, antibacterial agent, reinforcing agent, plasticizer, crosslinking agent and N,N-dimethylformamide into a reaction kettle, and stir at room temperature for 10-15 minutes to obtain an electrospinning solution; A2, adding the electrospinning solution into an electrospinning machine, electrospinning to obtain modified fibers, and performing post-treatment to obtain modified polyurethane fibers; A3. Use modified polyurethane fiber to weave to obtain a modified polyurethane layer (100).
2. The UV-resistant waterproof fabric for a leisure hat according to claim 1, characterized in that: In step A1, the stirring rate of the reactor is 80-120 rpm, and the amount ratio of modified polyurethane, inorganic crosslinking agent, antibacterial agent, reinforcing agent, plasticizer, crosslinking agent and N,N-dimethylformamide is 12-15 g: 2-3 g: 0.5-0.8 g: 0.5-0.8 g: 0.5-0.8 g: 0.3-0.5 g: 70-80 mL; In step A2, the electrospinning operation includes: pouring the electrospinning solution into the ejector of the electrospinning machine, setting the voltage of the electrospinning machine to 15-25 kV, setting the spinning distance to 10-20 cm, controlling the flow rate to 0.5-1 L / h, and spinning to obtain modified fibers.
3. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 1, characterized in that: The preparation method of the modified polyurethane comprises the following steps: B1. Add 2,4-dihydroxybenzophenone, N,N-dimethylformamide and dibutyltin dilaurate into a reaction kettle and stir. The temperature of the reaction kettle is raised to 50-60° C., 3,3-dichlorobiphenyl 4,4-diisocyanate solution is added dropwise into the reaction kettle, and the reaction is carried out by heat preservation for 40-60 minutes. An inorganic crosslinking agent is added into the reaction kettle, and the reaction is carried out by heat preservation for 20-30 minutes to obtain a composite polyurethane solution. B2. Add the composite polyurethane solution, 3-trifluoromethylpropiophenone, acetic acid and tetrahydrofuran into a reaction kettle, raise the temperature of the reaction kettle to 40-50° C., keep the temperature for 2-4 hours, and perform post-treatment to obtain a modified polyurethane.
4. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 3, characterized in that: In step B1, the stirring rate of the reactor is 80-120rpm, the amount ratio of 2,4-dihydroxybenzophenone, N,N-dimethylformamide, dibutyltin dilaurate, 3,3-dichlorobiphenyl 4,4-diisocyanate solution and inorganic crosslinking agent is 3-5g:20-30mL:0.1-0.3g:10-15mL:2-4g, and the 3,3-dichlorobiphenyl 4,4-diisocyanate solution is prepared by mixing 3,3-dichlorobiphenyl 4,4-diisocyanate and N,N-dimethylformamide in an amount ratio of 2-3g:6-10mL.
5. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 3, characterized in that: The preparation method of the inorganic crosslinking agent comprises the following steps: C1. Add butyl titanate and anhydrous ethanol into a reactor and stir. After stirring at room temperature for 15-20 minutes, continue to drop deionized water. After the temperature of the reactor is raised to 50-60°C, use 1-2 mol / L ammonia solution to adjust the system pH to 8-9. Keep the temperature for 36-48 hours to obtain titanium gel. After post-treatment, obtain nano titanium dioxide particles. C2. Add nano titanium dioxide particles, N-aminoethyl-3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and anhydrous ethanol into a reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain an inorganic crosslinking agent.
6. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 5, characterized in that: In step C1, the stirring rate of the reactor is 80-120rpm, and the dosage ratio of butyl titanate, anhydrous ethanol and deionized water is 3-6g:30-40mL:10-20mL; in step C2, the dosage ratio of nano-titanium dioxide particles, N-aminoethyl-3-aminopropyltriethoxysilane, saturated sodium hydroxide solution and anhydrous ethanol is 6-8g:2-3g:0.3-0.5mL:30-40mL.
7. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 1, characterized in that: The preparation method of the anti-ultraviolet hydrophobic layer comprises the following steps: D1, add trans-3-(trimethylsilyl)allyl alcohol, 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, azobisisobutyronitrile and dimethyl sulfoxide into a reaction kettle, raise the temperature of the reaction kettle to 70-80°C, keep the temperature for 2-4 hours, and obtain a modified liquid precursor; D2, adding the modified precursor liquid, 2,4-dihydroxybenzophenone and triethylamine into the reaction kettle, raising the temperature of the reaction kettle to 50-60°C, and keeping the temperature for 20-30 minutes to obtain the modified liquid; D3. Place the modified polyurethane layer (100) in a mold, mix the hydrophobic liquid and evenly coat the surface of the modified polyurethane layer (100) with a coating thickness of 40-50 μm, cure at high temperature to obtain a modified layer, and post-treat to obtain an anti-ultraviolet hydrophobic layer (200).
8. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 7, characterized in that: In step D1, the amount ratio of trans-3-(trimethylsilyl)allyl alcohol, 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, azobisisobutyronitrile and dimethyl sulfoxide is 4-5g:8-10g:2-3g:0.3-0.5g:60-80mL; in step D2, the amount ratio of modified precursor solution, 2,4-dihydroxybenzophenone and triethylamine is 15-20mL:2-3g:0.3-0.5g; in step D3, the hydrophobic liquid is prepared by mixing the modified liquid and acetic acid in an amount ratio of 50-60mL:3-5mL.
9. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 1, characterized in that: The preparation method of the moisture permeable lining layer (300) is as follows: after placing the anti-ultraviolet hydrophobic layer (200) toward the bottom of the mold, adding the modified moisture permeable liquid into the atomizer, spraying it onto the modified polyurethane layer (100) after atomization, with the spraying thickness of 15-20 μm, and obtaining the moisture permeable lining layer (300) after curing.
10. The anti-ultraviolet waterproof fabric for a leisure hat according to claim 9, characterized in that: The modified moisture permeable liquid is prepared by preparing polyurethane, polyacrylic acid resin, polyethylene glycol and deionized water according to the dosage ratio of 50-60g:10-20g:2-5g:20-30mL.
Citation Information
Patent Citations
A kind of thermoplastic polyurethane fabric and its preparation method and application
CN114274642B
Cited By
Heat-preservation and moisture-permeable regenerated fiber fabric and preparation method thereof
CN120738927A
Thermal and moisture permeable regenerated fiber fabric and method for manufacturing the same
CN120738927B